2011
DOI: 10.1007/s10641-011-9790-6
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the upper estuary as a nursery ground for fishes in Ariake Bay, Japan

Abstract: To examine the importance of the upper estuarine areas of Ariake Bay as a nursery ground for fish, assemblages of larvae and juveniles were compared among various aquatic habitats. The upper estuaries of the bay (the Rokkaku and Hayatsue estuaries) are brackish, highly turbid waters with high tidal velocities, and differ substantially from the Isahaya area, which has been separated from the bay by a man-made dike, to the middle estuary (the Kikuchi estuary). Abundances of larvae and juveniles were higher in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…New records support what is known about the habitat preferences of H. mohnikei , that it lives in shallow waters, predominantly in seagrass (Lourie et al ., ) with other syngnathid species (Yagi et al ., ; Choi et al ., ; Lipton & Thangaraj, ; Zhang et al ., ), while expanding its habitat range to include mangroves, oyster beds and mussel farms. Such preferences should raise concern, as H. mohnikei lives in the same habitats as other seahorse species ( H. kuda, H. spinosissimus and H. trimaculatus ) considered Vulnerable by the IUCN Red List (IUCN, ).…”
Section: New Records Of Hippocampus Mohnikei From Cambodia Malaysiamentioning
confidence: 99%
See 1 more Smart Citation
“…New records support what is known about the habitat preferences of H. mohnikei , that it lives in shallow waters, predominantly in seagrass (Lourie et al ., ) with other syngnathid species (Yagi et al ., ; Choi et al ., ; Lipton & Thangaraj, ; Zhang et al ., ), while expanding its habitat range to include mangroves, oyster beds and mussel farms. Such preferences should raise concern, as H. mohnikei lives in the same habitats as other seahorse species ( H. kuda, H. spinosissimus and H. trimaculatus ) considered Vulnerable by the IUCN Red List (IUCN, ).…”
Section: New Records Of Hippocampus Mohnikei From Cambodia Malaysiamentioning
confidence: 99%
“…Additionally mangrove, oyster and mussel farms were reported as habitat for this seahorse species. The new records support previous reports (Yagi et al ., ; Laksanawimol et al ., ; Lipton & Thangaraj, ; Zhang et al, ) that H. mohnikei co‐occur with congener species including Hippocampus kuda Bleeker 1852 and Hippocampus trimaculatus Leach 1814 and the pipefish genus Trachyrhamphus . The new sightings are the first reports of H. mohnikei inhabiting the same areas as Hippocampus spinosissimus Weber 1913 and two additional genera of pipefishes Acentronura and Halicampus .…”
Section: New Records Of Hippocampus Mohnikei From Cambodia Malaysiamentioning
confidence: 99%
“…Given the well-developed ETM incidental to large tidal ranges and long tidal intrusions, estuaries similar to the Chikugo River estuary could occur only in the innermost part of the Ariake Sea within Japan (e.g., Rokkaku River estuary, Yagi et al 2011).…”
Section: Implications For Estuarine Organismsmentioning
confidence: 99%
“…Coilia nasus is one of seven continental relict fishes occurring only in the Ariake Sea within Japan (Sato and Takita, 2000). Macrotidal estuaries characteristic of the innermost part of the Ariake Sea are thought to be primarily responsible for the survival of the relict fish populations after the isolation of the Japanese Archipelago from the Eurasian Continent caused by marine transgressions (Sato and Takita, 2000;Hibino et al, 2002;Yagi et al, 2011). Reproduction of the relict C. nasus population depends greatly on the Chikugo River estuary (Takita, 1967b;Matsui et al, 1986b), although sporadic reproduction has been observed in other estuaries of the Ariake Sea (Igita, 1986;Yagi et al, 2011).…”
Section: Implications For the C Nasus Populationmentioning
confidence: 99%
“…Macrotidal estuaries characteristic of the innermost part of the Ariake Sea are thought to be primarily responsible for the survival of the relict fish populations after the isolation of the Japanese Archipelago from the Eurasian Continent caused by marine transgressions (Sato and Takita, 2000;Hibino et al, 2002;Yagi et al, 2011). Reproduction of the relict C. nasus population depends greatly on the Chikugo River estuary (Takita, 1967b;Matsui et al, 1986b), although sporadic reproduction has been observed in other estuaries of the Ariake Sea (Igita, 1986;Yagi et al, 2011). Given high fishing pressure on migrating adults during the spawning season (Takita, 1967b;Yoshimoto and Kitajima, 1993), effective fishing regulations are necessary to preserve the relict C. nasus population.…”
Section: Implications For the C Nasus Populationmentioning
confidence: 99%